Measuring Disparities in the Impact of COVID‐19 on Pediatric Mental Health in Primary Care Settings - Cecilia Rogers; Katherine Boguszewski; Angela Gummadi; Mark Conaway; Laura Shaffer; Irène Mathieu (Mental Health Science)
ABSTRACT The purpose of this study is to examine disparities in mental health diagnoses, depression screening, and depressive symptoms in pediatric primary care settings before and during the COVID‐19 pandemic, and to evaluate the use of electronic health records to study temporal trends in pediatric mental and behavioral health (MBH). This is an IRB‐approved, retrospective study of pediatric patients (n = 11,001) who visited three primary care sites at an academic medical center before (2017–2019) and during (2020–2022) the COVID‐19 pandemic. We used logistic regression to compare prevalence of diagnoses, depression screening, and depression symptom scores among demographic groups. This study demonstrates an increase in both PHQ‐9A screening rates and average scores from 2017–2019 to 2020–2022. Despite an increase in overall PHQ‐9A scores, prevalence of mental health diagnoses is lower in 2020–2022 compared to 2017–2019. There were significant disparities in common mental health diagnoses, including higher rates of psychological distress among lower income patients, both before and during the pandemic. In both cohorts, patients classified as African American, Asian, or Other racial groups had a lower prevalence of diagnoses compared to Caucasian patients. However, patients marked as having multiple racial groups had greater levels of diagnoses. There were also lower screening rates among Hispanic patients. Gender non‐conforming patients had a significantly larger burden of psychological distress. This suggests a need for greater equity in routine MBH screening and additional research to better understand the underlying social determinants that may be driving the greater mental health burden for certain marginalized youth. This study also highlights the strengths and challenges of utilizing EHR data to characterize disparities in pediatric mental illness. Although the nature of care delivery in an academic medical center clinic and the limitations of the EHR for collecting relevant data present challenges to this measurement, the EHR is nevertheless a promising tool for measuring and tracking pediatric mental health disparities.